Temporal changes in periphytic meiofauna in lakes of different trophic states - Kurt Pettersson (Journal of Limnology, 2012)
Meiofaunal organisms in the periphyton of stony hard-substrates (epilithon) were studied in three Swedish lakes with different trophic states (oligo-, meso- and eutrophic) with respect to seasonal successions in abundance, biomass, and production. Over a period of 2 years, the meiofaunal population of all three lakes fluctuated greatly, with densities varying up to nine-fold within a season. In the oligotrophic lake, a significant decrease in meiofauna in winter was striking, whereas in the other two lakes, richer in nutrients, there was a pronounced peak in early summer. Although the lakes, on average, did not differ in epilithic organic and inorganic material, the differences in meiofaunal abundance, biomass, and production were significant. Correlation analysis revealed that altogether the meiofaunal biomass was positively related to the lakes’ trophic state (total phosphorus), while the meiofaunal abundance and production along the trophic spectrum displayed a humped-shape distribution, with maximum values measured in the mesotrophic Lake Erken (1324 ind cm-2 and 2249 mg DW cm-2 y-1). Nematodes were the dominant meiofaunal group in the epilithon of all three lakes, accounting for up to 58% in abundance, 33% in biomass and 55% in production of the whole meiofaunal community. However, their relative importance tended to decrease with increasing trophic state. Beside nematodes, rotifers, oligochaetes, copepods and tardigrades were also found in large numbers in the epilithon. Overall, the results demonstrated that, due to their high abundance, biomass, and production, meiofaunal organisms play an important role in epilithic communities.